Mechanical and Numerical Assessment of Localized Soil Voids Under PCCP Joints - Haizhen Li; Xin Feng; Ankui Hu (Buildings)
Uniform support from the surrounding soil is important for maintaining the stable operation of buried pipelines. For segmented prestressed concrete cylinder pipe (PCCP), localized soil voids around the joint due to leakage or engineering activities make the pipe unsupported partially and threaten its integrity and strength. In this paper, the impact of a localized soil void on a pipe joint is qualitatively assessed using a beam-on-elastic-spring approximation model. It further provides quantitative analysis through a nonlinear finite element (FE) model of PCCPs and the surrounding soil. The derived algebraic solutions indicate that a unilateral local void induces shear force and rotation at the joint, whereas shear force becomes negligible when the void spans the joint, leading to increased rotation. Moreover, the rotation angle shows a positive correlation with soil load and a negative correlation with pipe diameter. Numerical analysis reveals that void elongation along the pipe length has a more pronounced effect on structural response than void depth and angle. When the void length reaches 2.5 m, the maximum principal stress on the mortar layer of the PCCP increases approximately eight-fold compared to the scenario without voids. Due to the rigidity and safety factor of the PCCP, small voids in the bedding typically do not cause immediate pipe damage or joint leakage; however, they can significantly alter the stress distribution within both the pipe and surrounding soil. As the void develops, the soil may collapse and compromise support, leading to additional secondary disaster risks and potential threats to pipeline safety. This research emphasizes the importance of effective pipe-soil interactions and provides theoretical insights for developing repair strategies for PCCP.